PERAN ORANG TUA DALAM MENINGKATKAN PENDIDIKAN ANAK DI DESA PIASAK HILIR KECAMATAN SELIMBAU - Dodi Pratama; Izhar Salim; Supriadi Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
AbstractThe title of the thesis is "the role of the parents in raising children's education in the village of piasak sub-district of lower selimbau". 1) how is the role of parents as a motivator in improving education in the village of piasak sub-district of lower selimbau. 2) how is the role of parents as a facilitator in improving education in the village of piasak sub-district of lower selimbau. 3) how is the role of parents as mediators in improving the education of children in the village of piasak sub-district of lower selimbau. This research uses qualitative research methods in the form of a descriptive. Data collection tools using the guidelines of observation, interview and documentation study guidelines. The research results show (1) the existence of Already there is the role of parents in the form of home study guide. (2) it is proved with the granting of facilities to children as special study room at home and place store school supplies. (3) it is proven by parents who have always been a medium of communication and interaction in the Guide and teach children. Key words: the role of parents, child's education